Image Processing Techniques and its Application in Water Transport through Fabrics (Journal of Fiber Bioengineering and Informatics, 2018)
With the development of new synthetic fibres it is significant to study water transport through the fabric. Vertical wicking test is usually used to understand this fabric property. But the method for gaining parameters is still done manually at present. This paper will report an image processing technique on water transport through fabrics. Fabric images during wicking are shot for every 1min in 30mins. Every image can be divided into two areas to indicate fabric dryness and wetness. Finally, the wicking height can be calculated to understand water transport through the fabric. Considering the distortion of the vertical object image size far away from optical axis it is necessary to modify wicking height. Based on the vertical wicking measurement for fabric, the modification method took 300 mm height of the distortion image that was divided by 1 mm. A modifier formula was deduced based on geometry. It can improve the precision of wicking height obtained by image processing techniques. An application example is also described in this paper. Some fabrics were proved to have good water absorbing quality and moisture management. From the curve of the wicking height based on image processing techniques, initial wicking rate can explain the water absorbing quality and the maximum wicking height is used to illustrate moisture management.
Keywords: Image processing; vertical measurement; revising method; moisture absorbable and breathable fabric